2021
DOI: 10.3390/plants10020358
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bagging on the Development and Quality of Fruits

Abstract: Fruit quality is certainly influenced by biotic and abiotic factors, and a main quality attribute is the external appearance of the fruit. Various possible agronomical approaches are able to regulate the fruit microenvironment and, consequently, improve fruit quality and market value. Among these, fruit bagging has recently become an integral part of fruits’ domestic and export markets in countries such as Japan, China, Korea Australia and the USA because it is a safe and eco-friendly technique to protect frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 97 publications
1
44
1
Order By: Relevance
“…Organic acids, being the important constituent of fruit taste along with sugars, strongly influence the organoleptic quality of fruits [4,5]. The sugar-acid ratio is one of the important indicators to measure the flavor and maturation of fruit and is mainly affected by organic acid contents [6][7][8][9]. Many studies have been reported to ascertain compositional changes in passion fruit, and most of these studies have focused on the volatile compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids, being the important constituent of fruit taste along with sugars, strongly influence the organoleptic quality of fruits [4,5]. The sugar-acid ratio is one of the important indicators to measure the flavor and maturation of fruit and is mainly affected by organic acid contents [6][7][8][9]. Many studies have been reported to ascertain compositional changes in passion fruit, and most of these studies have focused on the volatile compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another very important factor in bagging is that it may increase the size of the mangoes compared to those non-bagged, which would allow bagging mangoes to be sold at a higher price [29]. In this sense, as our results suggest, fruit bagging is a physical technique that can be a very cost-effective and successful component of IPM for those small-scale Spanish mango producers who sell their organic fruit in selected European markets and expect to receive better prices for more quality and environmentally sustainable production [23,51].…”
Section: Discussionmentioning
confidence: 59%
“…According to Ali et al [23], fruit bagging is a relatively simple, secure, and environmentally friendly practice that reduces pest and disease damage and improves the appearance and physicochemical properties of the fruit. However, this cultural control measure can be an expensive pest management option on commercial orchards due to the time and labor required to set the bags on the fruit [17,29,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blend of bioethanol with 95% of petroleum oil can reduce about 90% of CO2 and 60-80% SO2 (Makur and Birhanu, 2020). Monosaccharides e.g., sucrose, glucose are the building blocks for the production of bioethanol from juices of crops containing free sugar in the presence of microorganisms via fermentation (Ali et al, 2021a;Ali et al, 2021b). Feedstock to produce bioethanol is sugar crops and starch that are 60% and 40% respectively (Zabed et al, 2014).…”
Section: Introductionmentioning
confidence: 99%